2017
DOI: 10.1111/apce.12176
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Governance in Social Enterprises in the Netherlands – A Case Study

Abstract: An element that policymakers and academics often believe to be constitutive in the governance of a social enterprise is the use of inclusive and responsible decision-making processes. This entails the involvement of various categories of stakeholders. In this paper, a case study is used to explore how a work integration social enterprise based in the Netherlands, AutiTalent BV, has organized its governance. The Netherlands has not developed legislation specifically dealing with social enterprises, in contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Colenbrander, Argyrou, Lambooy, and Blomme (2017) examine how inclusive and participatory governance is realized in a Dutch social enterprise in terms of processes and structures and concluded that its governance has an informal character and focuses on a free flow of information between employees and management:
“we have a very active view on staff engagement in the decision‐making of the business, so staff can also apply to become members of the company and, therefore, have a say in its say in strategy and direction” (SE12).
“everyone is approachable… from myself and Senior Management and down to shop floor and trainees. So, I think that provides quite a transparent culture” (SE05).
…”
Section: Results and Discussion Of Resultsmentioning
confidence: 99%
“…Colenbrander, Argyrou, Lambooy, and Blomme (2017) examine how inclusive and participatory governance is realized in a Dutch social enterprise in terms of processes and structures and concluded that its governance has an informal character and focuses on a free flow of information between employees and management:
“we have a very active view on staff engagement in the decision‐making of the business, so staff can also apply to become members of the company and, therefore, have a say in its say in strategy and direction” (SE12).
“everyone is approachable… from myself and Senior Management and down to shop floor and trainees. So, I think that provides quite a transparent culture” (SE05).
…”
Section: Results and Discussion Of Resultsmentioning
confidence: 99%
“…Works on the social enterprise-stakeholder relationship discuss the importance and constraints of balancing the interests of stakeholders and provide theoretical explanations for stakeholder participation. According to Colenbrander et al (2017), involving multiple stakeholders is imperative for the survival of social enterprises. It can provide them with expertise, legitimacy, and access to resources, and help them identify social needs.…”
Section: Participatory Governance In the Social Enterprise Researchmentioning
confidence: 99%
“…3. In the third group of contributions, participatory governance is not regarded simply as an organizational concept but also as a legal and political one (Spear, Cornforth and Aiken, 2009;Colenbrander et al, 2017). From this perspective, the implementation of participatory governance models also depends on the existence of appropriate legal frameworks.…”
Section: Participatory Governance In the Social Enterprise Researchmentioning
confidence: 99%
“…In the case of NPOs, the mission (Battilana, Sengul, Pache, & Model, 2015; Doherty et al., 2014) and the nature of human resources (Barrenechea‐Mendez & Ben‐Ner, 2017; Ben‐Ner & Ren, 2015) can particularly affect the content of the HRM practices adopted. As regards the external environment, institutions (Akingbola, 2013) including legislation (Colenbrander, Argyrou, Lambooy, & Blomme, 2017) and the economic context particularly shaped by market pressures (Kaye, Jans, & Jones, 2011) play a prominent role.…”
Section: Work Integration Social Enterprises and Their Compatibility mentioning
confidence: 99%
“…Regarding the institutional context, commercial WISEs in the Italian context must employ at least 30% disadvantaged workers by law. The prevalent business model is that of social cooperatives, therefore applying member democratic control, limited‐profit distribution, and an asset lock, mirroring growth strategies based on surplus reinvestment with the primary aim to benefit marginalized workers and the community in a stable way (Borzaga & Tortia, 2006; Colenbrander et al., 2017). At the same time, fiscal relief is assured by the state over hired disadvantaged people’ wages.…”
Section: Work Integration Social Enterprises and Their Compatibility mentioning
confidence: 99%